Aransemen Lagu Buku Ende No. 585 “Somba Ma Jahowa” Dalam Instrumen Taganing - Lamsa J Sihombing (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The aim of this research is to develop the song ''BE. 588 Somba Ma Jahowa Debata” into the Taganing arrangement and the motif in this song still uses the original melody from the song but there is a slight change in tempo from MM 120 to MM 98, and the rhythm aims to be more wise and pleasant to listen to. This research uses qualitative descriptive research, namely by describing the